Penguatan Kompetensi dan Soft Skills melalui Implementasi Kurikulum Merdeka di MTsN 1 Merangin - Hidayatul Fadliah; Putri, Riska Meisyi; Sarinah, Sarinah (Jurnal Pengabdian Kepada Masyarakat, 2025)
The Independent Curriculum provides educators with flexibility in designing learning that focuses on developing students' competencies and strengthening their character. However, its implementation in various educational units, including MTs Negeri 1 Merangin, still faces challenges, particularly in increasing teacher capacity to implement learning that fosters students' soft skills. This Community Service activity aims to improve teachers' pedagogical and professional competencies through the implementation of project-based learning in accordance with the principles of the Independent Curriculum. The method used was Participatory Action Research (PAR) with stages of training, mentoring, and evaluation. Data were collected through observation, interviews, and questionnaires, then analyzed descriptively quantitatively. The activity was packaged in an extracurricular performance involving OSIM, ROHIS, UKS, PMR, PIK-R, and Pramuka. The results showed an increase in teacher understanding, a collaborative culture, and strengthening of students' character and soft skills.